Concept of the family by children raised in an orphanage - Morano, Rose Ann V.
This study identifies the different concepts of family developed by children living in an orphanage. The respondents of this study were nine orphans aged 8-10 years old from Manila Boys Town Complex located in Marikina City. They have been staying in the orphanage for at least three years. The respondents do not have any form of communication with their biological families. A structured interview was used to get the concept of the family from the respondents. They were also requested to draw their concept of family. Responses were analyzed using in-depth analysis. Findings of the study showed that the respondents' concept of a family is a social entity that is always happy. Consequently, they defined a happy family as being together and the family has the ability to render companionship to its members by helping each other. The findings of the study also revealed that perceived maternal responsibilities of respondents were to perform household chores while the fathers are the breadwinners of the family, other members of the family were expected to assist in other household chores.